2022
DOI: 10.1186/s12913-022-07861-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient and family involvement in Choosing Wisely initiatives: a mixed methods study

Abstract: Background Patients are important stakeholders in reducing low-value care, yet mechanisms for optimizing their involvement in low-value care remain unclear. To explore the role of patients in the development and implementation of Choosing Wisely recommendations to reduce low-value care and to assess the likelihood that existing patient resources will change patient health behaviour. Methods Three phased mixed-methods study: 1) content analysis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Adults who transition to persistent or chronic critical illness have complex recovery and rehabilitative care needs requiring a shift in care goals and care planning [1]. Treatments considered important to the safe and effective management of acute critical illness such as continuous hemodynamic monitoring, frequent blood testing, and use of sedative drugs may be comparatively less appropriate in patients with persistent or chronic critical illness and equate to low-value care [2]. Despite awareness of differences in care needs and the known burden of persistent and chronic critical illness on patients, their family members, and the healthcare system, [3], there are few tools (e.g., checklists or protocols) or quality metrics specific to this patient population to aid in the delivery of high quality care.…”
Section: Introductionmentioning
confidence: 99%
“…Adults who transition to persistent or chronic critical illness have complex recovery and rehabilitative care needs requiring a shift in care goals and care planning [1]. Treatments considered important to the safe and effective management of acute critical illness such as continuous hemodynamic monitoring, frequent blood testing, and use of sedative drugs may be comparatively less appropriate in patients with persistent or chronic critical illness and equate to low-value care [2]. Despite awareness of differences in care needs and the known burden of persistent and chronic critical illness on patients, their family members, and the healthcare system, [3], there are few tools (e.g., checklists or protocols) or quality metrics specific to this patient population to aid in the delivery of high quality care.…”
Section: Introductionmentioning
confidence: 99%
“…Available at www.choosingwisely.org , it is a campaign to engage physicians and patients in conversations about unnecessary tests, treatments, and procedures [ 3 ]. To be effective, it is suggested that low-value versus high-value care should be discussed during the clinical encounters between patients, their families, and physicians [ 4 ]. In the discussions, it is important to identify the barriers to patient involvement and adherence to high-value care, which include discussions about cost, outcomes, complications of interventions, and the implications that proper care, or a dearth of it, can have on their lives and livelihood.…”
mentioning
confidence: 99%